Enhancement of electrical conductivity of carbon nanotube sheets through copper addition using reduction expansion synthesis. (November 2020) - Earp, Brian; Dunn, Durward; Phillips, Jonathan; Agrawal, Richa; Ansell, Troy; Aceves, Patrick; De Rosa, Igor; Xin, Wenbo; Luhrs, Claudia
Graphical abstract: Highlights: CNT sheet electrical conductivity improved through copper particulate deposition. Cu salt reduction via Reduction Expansion Synthesis promotes metal attachment on CNT. Improvement of bulk CNT electrical conductivity using a rapid and scalable method. Abstract: The ability to translate the high electrical conductivity of individual carbon nanotubes to bulk carbon nanotube materials has proven challenging. In this work, we present the use of reduction expansion synthesis to attach copper nanoparticles to the surface of tubes within carbon nanotube sheets. Those metallic particulates serve as a link between the tube strands in the carbon nanotube network and promote an increase in electrical conductivity. The reduction expansion synthesis process included the introduction of copper salts into the carbon nanotube structure and thermal treatment of the sheets in the presence of urea, under inert atmospheres. As a result, through the reduction process promoted by the urea decomposition byproducts, copper nanoparticles directly nucleate on the nanotube surface. The enhanced conductive nature of the Cu-carbon nanotube sheets observed establishes reduction expansion synthesis as an inexpensive, rapid and scalable alternative to increase the electrical conductivity of bulk carbon nanotube materials.